Closed-loop control with unannounced exercise for adults with type 1 diabetes using the Ensemble Model Predictive Control. (August 2019) - Garcia-Tirado, Jose; Corbett, John P.; Boiroux, Dimitri; Jørgensen, John Bagterp; Breton, Marc D.
Highlights: Subject's exercise behavior is characterized through the net effect method. Hypoglycemia prevention during and after a single moderate exercise bout. Asymmetric objective function to cope with hypoglycemia. In silico testing through the last version of the FDA-accepted UVa/Padova simulator. Abstract: This paper presents an individualized Ensemble Model Predictive Control (EnMPC) algorithm for blood glucose (BG) stabilization and hypoglycemia prevention in people with type 1 diabetes (T1D) who exercise regularly. The EnMPC formulation can be regarded as a simplified multi-stage MPC allowing for the consideration of N en scenarios gathered from the patient's recent behavior. The patient's physical activity behavior is characterized by an exercise-specific input signal derived from the deconvolution of the patient's continuous glucose monitor (CGM), accounting for known inputs such as meal, and insulin pump records. The EnMPC controller was tested in a cohort of in silico patients with representative inter-subject and intra-subject variability from the FDA-accepted UVA/Padova simulation platform. Results show a significant improvement on hypoglycemia prevention after 30 min of mild to moderate exercise in comparison to a similarly tuned baseline controller (rMPC); with a reduction in hypoglycemia occurrences (<70 mg/dL), from 3.08 % ±3.55 with rMPC to 0.78 % ±2.04 with EnMPC ( P < 0.05).